Differences Between Faculty and Students' Perceptions of the Disruptiveness of Electronic Device Usage in the Classroom - Burnsed, Robbie Renee (William Carey University, 2017)
The purpose of this research study was to explore the differences between faculty and students’ perceptions of electronic device usage in the classroom. A quantitative cross-sectional design was utilized with an independent samples two- tailed t-test to study the disruptiveness of electronic device usage in the classroom. Participants were asked to complete a survey concerning device usage in the classroom. The survey was sent to faculty and students of all disciplines and levels of education at two universities in a southeastern state in the United States. The literature review included electronic device usage, social media usage, benefits and challenges of electronic device usage in the classroom, and electronic device usage as helpful tool or a hindrance to the teaching and learning process. Findings from the study indicated that faculty perceived that electronic device usage was more disruptive in the classroom to the teaching and learning process than students. Recommendations included future research on technology usage in the classroom and ways to assist with decreasing the disruptions electronic devices cause in the teaching and learning process. Recommendations also included a specific approach of focusing on technology usage in the teaching and learning process based on generational groups.